The Tainos: Rise and Decline of the People Who Greeted Columbus by Irving Rouse, Yale University Press, New Haven. 1992 - James A. Delle (Bulletin of the History of Archaeology, 1993)
There are few people who can claim to command as much knowledge of the prehistory of the Caribbean as lrving Rouse. Professor Rouse began his field work in the Caribbean in the mid- 1930's; this book is his synthesis of the vast amount of information he has accumulated on the region in the half century that has elapsed since that time. In order to accomplish the tremendous task of interpreting nearly 6000 years of the region's prehistory, Rouse focused this book on the culture history of the Native American group known as the Tainos, the name given to the people who occupied much of the Caribbean upon the arrival of Europeans to the area in the 15th century AD.